ANALYSIS OF THE KALMAN FILTER METHOD ON A GYROSCOPE TO REDUCE NOISE TO IMPROVE RESPONSIBILITY IN A SHOOTING - Dekki Widiatmoko; Rian Putra Eka Setiawan; Hairani Hairani; rokhim utomo (Elektronika Sistem Senjata, 2025)
This study aims to analysis how effective the Kalman Filter method is in reducing noise in gyroscope signals to improve the responsiveness of a shooting simulator. By using the Kalman Filter, the data from the gyroscope becomes more accurate, leading to a more realistic shooting simulation experience. The clearer signal not only improves orientation accuracy but also reduces the system's response time, making the simulator faster and more precise in reacting to user inputs. The results show that the Kalman Filter significantly enhances the performance of the shooting simulator, which is crucial in military and security settings where accuracy and quick response are essential.